Effect of Thermal Radiation on Magneto-Convection of a Micropolar Nanoliquid towards a Non-Linear Stretching Surface with Convective Boundary - Jagan, K.; Sivasankaran, S.; Bhuvaneswari, M.; Rajan, S. (International Journal of Engineering and Technology, 2018)
The objective of this paper is to analyze the effect of thermal radiation on MHD mixed convection flow of a micropolar nanoliquidÂ Â towards a non-linear stretching surface with convective boundary condition. The governing equations are converted into non-linearÂ Â Â ordinary differential equations by using suitable similarity transformations. The homotopy analysis method is used for solving the non-linear ordinary differential equations. The temperature profiles increase due to increase in thermal radiation parameter. The microrotationÂ Â profile increases when boundary parameter is increased. Also, the skin friction coefficient and local Nusselt are plotted for variousÂ Â Â parameters.Â Â